Modeling and analysis of McPherson suspension system - 219408 Mohd. Azley Mohd. Sim (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006